A second hadrosauroid dinosaur from the early Late Cretaceous of Zuoyun, Shanxi Province, China. (2nd January 2017) - Wang, Run-Fu; You, Hai-Lu; Wang, Suo-Zhu; Xu, Shi-Chao; Yi, Jian; Xie, Li-Juan; Jia, Lei; Xing, Hai
Abstract: A second basal hadrosauroid dinosaur, Zuoyunlong huangi gen. et sp. nov., is reported from the early Late Cretaceous Zhumapu Formation in Zuoyun County, Shanxi Province, northern China. Zuoyunlong preserves a partial right ilium and ischium and is unique in having a very short postacetabular process 50% as long as the iliac central plate. Our cladistic analysis recovers Zuoyunlong as the most basal Late Cretaceous hadrosauroid, with a sister taxon relationship with Probactrosaurus from the late Early Cretaceous of Inner Mongolia. Including Zuoyunlong, four Cenomanian basal hadrosauroids have been recorded, and the two taxa in North America ( Eolambia and Protohadros ) represent the earliest known hadrosauroids outside of Asia. In the light of the proposed phylogenetic topology and biogeographic data, the discovery of Zuoyunlong indicates that the first dispersal of hadrosauroids from Asia to North America probably happened around the boundary between the Early and Late Cretaceous.